1389. Economic Evaluation of Universal Varicella Vaccination in Mexico. (31st December 2020) - Chacon-Cruz, Enrique; Meroc, Estelle; Costa-Clemens, Sue Ann; Verstraeten, Thomas
Abstract: Background: Universal varicella vaccination (UVV) has proven to be cost-effective in countries where implemented. However, this has not yet been evaluated for Mexico. We assessed the cost-effectiveness of UVV in the Mexican Immunization Program from both healthcare and societal perspectives. Methods: The annual disease burden (varicella cases/deaths, outpatient visits, and hospitalizations) were derived from Mexican seroprevalence-published data adjusted to the 2020 country's population. The annual economic burden was calculated by combining disease with Mexican published unit cost data. Four different vaccination strategies were evaluated: 1. One dose of a single varicella vaccine at 1 year old; 2. Two doses of single varicella vaccine at 1 and 6 years; 3. One dose of a single varicella vaccine at 1 year, and quadrivalent measles-mumps-rubella-varicella vaccine (MMRV) at 6 years; 4. Two doses of MMRV at 1 and 6 years. We developed an economic model for each vaccination strategy where 20 consecutive birth cohorts were simulated. The impact of vaccination (number of avoided cases/deaths) was evaluated for a 20 years follow-up period based on vaccine effectiveness (87% and 97.4%), and assuming a 95% coverage. Subsequently, we estimated net vaccination costs, benefit-cost ratio (BCR), annual costs saved, cost-effectiveness ratio. Results: From annual disease burden estimation, avoided cases with one dose, and two doses were of 20, 570, 722 and 23, 029, 751, respectively. From the 20 years cohort, the yearly number of varicella cases was estimated at 2, 041, 296, and total costs at 115, 565, 315 (USD) (healthcare perspective) and 165, 372, 061 (healthcare and societal perspectives). Strategies 1 and 2 were found to be cost-saving (BCR >1) (Figure 1), and strategy 3 to be cost-effective (CE) (1539 per Life Year Gained). Strategy 4 was not CE. Strategies 1 and 2 would allow saving annually 53.16 million and 34.41 million, respectively, to the Mexican society. FIGURE 1 Conclusion: 1.The disease and economic burden of varicella in Mexico are high. 2.UVV with four different vaccination strategies results in a high reduction of cases. 3.From healthcare and societal perspectives, UVV was shown to be cost-effective (with strategy 3), and cost-saving (with strategies using one dose or two doses separately). Disclosures: All Authors : No reported disclosures